Gender-sensitive Science & Technology policy: Relevant? Needed? Marketable? - Mendonça, S. (II International Conference: Gender and Communication, 2014)
An intersection less studied : The expanded role of knowledge-based change in the contemporary world. Biases and identities of researchers , policy-makers, and stakeholders. Gender-responsive Science & Technology, Innovation & Entrepreneurship policy.